Analisis Pengaruh Hak Upah Kerja Bagi Peningkatan Kinerja Karyawan Detik Sumsel - Dwi Putri Maharani; Nuraida; Ahmad Harun Yahya (GLOBAL SCIENTS PUBLISHER, 2024)
The background of this research is the problem of the right to wages and the obligations of basic tasks and functions in each field, where wages are a worker's right to meet their living needs, both primary and secondary needs. Work has obligations to the employment company Detik Sumsel. So the author determined the title of this research regarding